2020
DOI: 10.2174/1871520619666191024115738
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K/Akt/NF-kB Signaling Mediates Swedish Snus Induced Proliferation and Apoptosis Evasion in the Rat Forestomach: Modulation by Blueberry

Abstract: Background and Objective: The present study was undertaken to ascertain whether the modulatory effects of blueberries on cell proliferation induced by Swedish snus in the rat forestomach epithelium is mediated via abrogation of the PI3K/Akt/NFκB signaling axis that regulates cell fate decision. Methods: The transcript and protein expression of genes involved in cell cycle progression and apoptosis, as well as canonical PI3K/Akt/NF-κB signaling pathways, were analyzed by qRT-PCR, immunoblotting and ELISA. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…Among the 12 differential exosome miRNAs target genes obtained by KEGG and Go (CCR7/CX3CR1/ CXCR2/CXCR3/CXCR5/AKT1/CCL5/CXCL1/CXCL2/CXCL3/ MAPK3/NFkB1), we predicted that mir-885-3p targeted the regulation of AKT. As a classical molecule of the chemokine signaling pathway, AKT regulates the expression of downstream protein NFkB (44), which is consistent with KEGG functional enrichment results. Therefore, we hypothesized that the mir-885-3p-targeted regulation of the AKT/NFkB signaling pathway enhances the glucocorticoid sensitivity of OFs.…”
Section: Discussionsupporting
confidence: 88%
“…Among the 12 differential exosome miRNAs target genes obtained by KEGG and Go (CCR7/CX3CR1/ CXCR2/CXCR3/CXCR5/AKT1/CCL5/CXCL1/CXCL2/CXCL3/ MAPK3/NFkB1), we predicted that mir-885-3p targeted the regulation of AKT. As a classical molecule of the chemokine signaling pathway, AKT regulates the expression of downstream protein NFkB (44), which is consistent with KEGG functional enrichment results. Therefore, we hypothesized that the mir-885-3p-targeted regulation of the AKT/NFkB signaling pathway enhances the glucocorticoid sensitivity of OFs.…”
Section: Discussionsupporting
confidence: 88%
“…These results indicate that HSP might also induce apoptosis via the NF-κB signaling pathway. Moreover, some studies have reported that NF-κB is the downstream molecule in regulating apoptosis in the PI3K/Akt signaling pathway ( 25 , 31 ). Considering these findings collectively, we speculated upon the potential mechanism underlying HSP-induced apoptosis in GL261 cells ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the transcription levels of pro-apoptotic genes Bax and Fas and anti-apoptotic genes Bcl-2 and Bcl-xl were further determined using qRT-PCR; the results suggested that rBsCPI-1 has a dual regulatory effect mainly to promote apoptosis. Meanwhile, studies have shown that NF-κB has a dual regulatory effect on cell apoptosis [ 36 , 37 ]. Similarly, activated MAPK also regulates cell apoptosis by transferring extracellular stimuli [ 38 40 ].…”
Section: Discussionmentioning
confidence: 99%